Pentingnya Pemahaman Emosi Dalam Proses Pembelajaran di MI Al-Masrhi Pangkalan Balai-Banyuasin - Mutyati Mutyati; Mardiah Astuti; Anita Dwi Kartika; Barkatilah Dafa Dwitasari; Aulia Rahmadanti; Aisya Sina Dewi; Ibrahim Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to understand the comprehension of emotions in the learning process at MI Al-Masrhi in Pangkalan Balai, Banyuasin Regency. The method used in this study is qualitative research with a descriptive approach. Data collection methods involve interviews with 12 respondents, including educators, school principals, students, and parents of students. Data collection also includes observations and documentation, while data analysis techniques encompass data collection, data presentation, and data verification. The research findings demonstrate the importance of emotional understanding for teachers in relation to students' learning. Teachers play a crucial role in being sensitive to students' emotions, helping them deal with stress, anxiety, or negative feelings that can disrupt the learning process. Emotional understanding can aid teachers in identifying emotional factors that can affect students' learning motivation. Teachers who understand their students' emotions can build positive relationships with them, and emotional comprehension contributes to the emotional well-being of both students and teachers, enabling teachers to engage students in the learning process through participative methods